2003
DOI: 10.2166/ws.2003.0200
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ultrafiltration as a pretreatment of reverse osmosis membranes for surface seawater desalination

Abstract: Pre-treatment of seawater feeding reverse osmosis (RO) membranes is a key step in designing desalination plants, especially when treating surface seawater with highly variable quality. The objective of the study was to assess the potential of ultrafiltration (UF) pre-treatment prior to RO for desalting seawater with high-fouling tendency. A UF pilot plant equipped with an Aquasource membrane was directly operated on Gibraltar surface seawater in dead-end mode. The competitiveness of UF pre-treatment towards co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This increasing trend in research and real time installations in RO plants is due to the various shortcomings associated with conventional pretreatment techniques, as discussed in section 2.1.7. More often, colloids and suspended particles pass through the conventional filters and contribute to RO membrane damage [128]. Therefore, the use of large pore size membranes in MF (0.1-0.35µm), UF (0.01-0.05µm) and NF (1-2nm) to pretreat RO water becomes essential [4].…”
Section: Membrane Pretreatment Techniquesmentioning
confidence: 99%
“…This increasing trend in research and real time installations in RO plants is due to the various shortcomings associated with conventional pretreatment techniques, as discussed in section 2.1.7. More often, colloids and suspended particles pass through the conventional filters and contribute to RO membrane damage [128]. Therefore, the use of large pore size membranes in MF (0.1-0.35µm), UF (0.01-0.05µm) and NF (1-2nm) to pretreat RO water becomes essential [4].…”
Section: Membrane Pretreatment Techniquesmentioning
confidence: 99%
“…Membrane processes have rapidly developed since the 1960s (D'souza & Mawson, 2005;Loeb & Sourirajan, 1963) and now surpass thermal processes in new plant installations (75% of new production capacity). Currently, RO membranes are made so that these can reject more than 99% salts (Brehant, Bonnelye, & Perez, 2003;Reverberi & Gorenflo, 2007). RO membrane technology has been developed for both brackish and seawater applications.…”
Section: Thermal or Membrane Desalinationmentioning
confidence: 99%
“…A new trend in pretreatment has been the movement toward using larger pore-size membranes (microfiltration (MF), ultrafiltration (UF), and nanofiltration (NF)) to use RO as a pretreatment to feed water that avoids the passage of colloids and suspended particles contributing to RO membrane fouling (Brehant et al, 2003). The membranes act as a defined barrier between the RO system and any suspended particles.…”
Section: Conventional and Membrane Pretreatment For Ro Feed Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Few recent works have also been published on coagulation/UF performed on seawater. Brehant et al (2003) studied the combination of UF with a pre-coagulation with ferric chloride at low dose (1 mg/L). They showed that coagulation helped in controlling membrane fouling.…”
Section: Introductionmentioning
confidence: 99%